Anatomic acromioclavicular and Coracoclavicular ligament reconstruction with allograft is effective for the management of non-acute acromioclavicular dislocations - Ruiz Ibán, Miguel Angel; Ruiz Díaz, Raquel; de Rus Aznar, Ignacio; Vaquero Comino, Carlos; Diaz Heredia, Jorge (Injury, 2023)
•In non-acute traumatic acromioclavicular dislocations, reconstruction of the acromioclavicular and coracoclavicular ligament with tendon allografts is effective and safe.•Loss of reduction is rare and can associate poorer clinical results.•Secondary tunnel widening develops often but does not seem to affect clinical outcomes. to analyze the short-term outcomes of an anatomical technique that reconstructs both the acromioclavicular and coracoclavicular ligaments with the help of a tendon allograft for the management of non-acute acromioclavicular dislocations. this is a prospective longitudinal study of a case series of subjects with symptomatic non-acute (>3 weeks) acromioclavicular dislocations surgically managed with an anatomical reconstruction of both the acromioclavicular and coracoclavicular ligaments using tibial tendon allografts. Outcomes were assessed with simple standardized radiographs and with the Constant-Murley, American Shoulder and Elbow Surgeons (ASES)-shoulder and Quick-DASH (Disabilities of the Arm, Shoulder and Hand) scales; also, the acromioclavicular joint stability and the scapulothoracic kinematics were assessed. a total of 19 subjects were assessed. There were no intraoperative or early postoperative complications. After a minimum two year follow-up (mean 3.12 years, [standard deviation 1.10 years]), there were significant improvements in all three of the scales: The Constant-Murley score increased from 65.4 (13.0) preoperatively to 92.6 (11.2) at the end of follow-up (p<0.001); the Quick-DASH score improved from 21.3 (6.73) to 13.0(4.58) (p<0.001); and the ASES-shoulder score increased from 56.6 (14.6) to 91.0 (9.86) (p<0.001). The AC joint was stable in both the vertical and the horizontal plane, without residual scapulothoracic dysfunction in 18/19 subjects at the end of follow-up. Only one patient presented a poor functional outcome, with loss of reduction, instability and persistent symptoms. Another subject suffered loss of reduction, though without functional repercussions. Two subjects had asymptomatic distal clavicle osteolysis and two developed radiographic osteoarthritis and were also asymptomatic. Moderate widening of the tunnels was observed in most patients: tunnel size after surgery was 5.1 (0.3) mm versus 5.8 (1.1) mm at the end of follow-up (p = 0.001) but widening was not correlated to final function. the anatomical reconstruction of the acromioclavicular and coracoclavicular ligament complexes with a tendon allograft yields excellent clinical outcomes when used in subjects with symptomatic non-acute acromioclavicular dislocations. Secondary tunnel widening, distal clavicle osteolysis and osteoarthritis might be of concern but do not affect clinical outcomes.